2012
DOI: 10.1063/1.3677360
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the levitation limits of dust particles within the sheath in complex plasma experiments

Abstract: Experiments are performed in which dust particles are levitated at varying heights above the powered electrode in a RF plasma discharge by changing the discharge power. The trajectories of particles dropped from the top of the discharge chamber are used to reconstruct the vertical electric force acting on the particles. The resulting data, together with the results from a selfconsistent fluid model, are used to determine the lower levitation limit for dust particles in the discharge and the approximate height … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 20 publications
6
52
1
Order By: Relevance
“…Time-independent biasing is used in plasma experiments for different purposes, namely for the measure of the ion and electron temperatures with electrostatic probes, 2,3 in plasma thrusters for space propulsion, 4 to study the effect of shear flow on turbulence, [6][7][8][9] for the study of dust particles, 5 and for the control of turbulence in magnetic fusion devices. [10][11][12] A bias may induce local perturbations of the plasma potential.…”
Section: Introductionmentioning
confidence: 99%
“…Time-independent biasing is used in plasma experiments for different purposes, namely for the measure of the ion and electron temperatures with electrostatic probes, 2,3 in plasma thrusters for space propulsion, 4 to study the effect of shear flow on turbulence, [6][7][8][9] for the study of dust particles, 5 and for the control of turbulence in magnetic fusion devices. [10][11][12] A bias may induce local perturbations of the plasma potential.…”
Section: Introductionmentioning
confidence: 99%
“…The intensity of each pixel (on an 8-bit scale) was then averaged across each horizontal row in order to obtain the emission intensity as a function of the height above the lower electrode. Figure 1a shows both curves obtained at a system pressure of 20 Pa and a driving potential amplitude of V RF = 30 V. The solid vertical line indicates the point where quasi-neutrality breaks, as determined by the growth of the electric force acting on the dust, which corresponds to the sheath edge [4]. The dashed vertical line indicates the point of maximum glow intensity.…”
Section: A Glow and The Force Profilementioning
confidence: 99%
“…It has been shown that electric force profiles can be used to locate the sheath edge [4]; however, optical emission from a plasma (when no dust is present) is also commonly used to determine the sheath edge. The dominant transition contributing to the optical emission in argon plasma at the low pressures and powers used in the following experiment is the atomic 5p-4s transition.…”
Section: A Glow and The Force Profilementioning
confidence: 99%
See 2 more Smart Citations